2011
DOI: 10.1002/maco.201106337
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical characterization of Ni47.7Ti37.8Nb14.5 shape memory alloy in artificial saliva

Abstract: Electrochemical corrosion behaviour of the studied Ni47.7Ti37.8Nb14.5 (NiTiNb) shape memory alloy was investigated for dental applications. An equiatomic NiTi alloy was used in some tests as reference material. Electrochemical techniques such as anodic potentiodynamic polarization, open circuit potential and electrochemical impedance spectroscopy (EIS) were employed. Experiments were carried out using artificial saliva. Very low passive current densities were obtained from the anodic polarization curve, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Shape memory alloys have a functionality that effectively represents a sensor and an actuator, which makes them a multifunctional material with many different applications . Among the shape memory alloys, NiTi shape memory alloys are being utilized with the most desirable amount of feedback in a number of applications , including biomedical and industrial applications . Nevertheless, the low transformation temperatures (−100 to 100 °C) and excessive production cost of NiTi alloys render their usage for many applications impractical, particularly for high‐temperature usage.…”
Section: Introductionmentioning
confidence: 99%
“…Shape memory alloys have a functionality that effectively represents a sensor and an actuator, which makes them a multifunctional material with many different applications . Among the shape memory alloys, NiTi shape memory alloys are being utilized with the most desirable amount of feedback in a number of applications , including biomedical and industrial applications . Nevertheless, the low transformation temperatures (−100 to 100 °C) and excessive production cost of NiTi alloys render their usage for many applications impractical, particularly for high‐temperature usage.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Nb content has no significant influence on thermal-induced transformation hysteresis of NiTiNb shape memory alloys. The thermal-induced transformation hysteresis of Ni 49 Ti 49 Nb 2 , Ni 48 Ti 48 Nb 4 , and Ni 47 Ti 47 Nb 6 shape memory alloys was determined as 16.3, 10.6, and 12.3 • C [12], respectively, which is similar to that of NiTi (10 • C) [15]. Furthermore, for the NiTiNb SMAs, the different Nb content leads to significant changes in microstructure [10] and phase transformation [12].…”
Section: Introductionmentioning
confidence: 67%
“…Therefore, to improve NiTi alloy, the Ni concentration can be reduced by replacing it with a third and fourth element, such as Ta, Nb, V, Sn. Mareci et al reported that the substituting of Ni with Nb in NiTiNb alloy increased the resistance of NiTi shape memory alloy to localized corrosion [22]. In another study, Balci et al found that the dendritic microstructure of the shape memory alloys prepared in different proportions were different in terms of composition, e.g., although Ti element has a higher ratio, from the EDX analysis and SEM images showed that the dendritic structure observed of in the Ni27Ti50Nb21V2 (at.%) alloy almost consist of Nb [23].…”
Section: Introductionmentioning
confidence: 99%